Medical Audit In The Perspective Of Remittances For Telemedicine Practices (Evaluation Of Law In Indonesia) (Journal of Namibian Studies : History Politics Culture, 2023)
This study is a normative legal research that focuses on evaluating the role of medical audit, telemedicine practice, and remittances in the context of digital health in Indonesia. This study uses a descriptive analytical m Keywords: Medical Audit, Telemedicine Practice, Remittance, Health Digitalization.ethod, with a philosophical and analytic approach, in understanding and evaluating the legal and practical challenges that exist in the implementation and enforcement of laws related to medical audits and telemedicine practices, as well as security and accountability in electronic money transfers. The results of the research indicate that while the existing legal framework provides a sound foundation, there are challenges in the application and enforcement of this law. The solutions found involve collaboration and coordination between the various parties involved, including governments, healthcare providers, technology companies, and communities. This research emphasizes the importance of a collaborative and proactive approach in realizing a sustainable and effective digitization of health in Indonesia .